Labor differences between people with congenital and adulthood acquired disability. Secondary analysis of the National Disability Survey - ENEDIS 2012 - Rojas-Villegas, Miguel (2021)
Objetive: To evaluate labor differences between people with congenital and adulthood acquired disability. Material and Methods: Secondary analytical cross-sectional study of the National Disability Survey (ENEDIS) - 2012. People between 14 and 65 years of age were included, grouping them according to their disability (congenital, early acquired, adulthood acquired). The final results of interest were considered: to have a job, being a dependent or independent worker, to have a contract and to have an income higher than the minimum living wage. Bivariate and multivariate analyzes were performed to evaluate the differences raised. Results: 16060 people were studied, 27,92% presented congenital disability, 10,45% early acquired and 61,63% adulthood acquired. It was found that those with adulthood acquired disability had a higher frequency of to have a job (34,93 vs 23,20 %, p <0,001), to have a contract (50,40 vs 27,74 %, p <0.001) and have income higher (18,18 vs 13,29 %, p = 0,048), with respect to people with congenital disability. When performing the multivariate analysis, the differences in economic income and type of contract decrease (p<0,05), but the probability of to have a job in adulthood acquired disability reverses from 51% more to 8% less (p = 0.057). Conclusions: People with adulthood acquired disability have more employment and income than those with congenital disability. Apparently this does not depend on the time of disability (which is less in adulthood acquired disability) but mainly to factors such as age, sex, level of education, region of residence and type of limitation.